One-pot synthesis of Zn-doped SnO2 nanosheet-based hierarchical architectures as a glycol gas sensor and photocatalyst. Issue 23 (21st June 2015) - Zhao, Qinqin; Deng, Xiaolong; Ding, Meng; Gan, Lin; Zhai, Tianyou; Xu, Xijin
<x xml:space="preserve">Abstract</x> Zn-doped SnO2 hierarchical architectures show high response and good selectivity to glycol and good selectivity to MB as a photocatalyst.